Pengaruh Penggunaan E-Wallet terhadap Pengelolaan Keuangan Karyawan PT Permodalan Nasional Madani (PNM) - Dede Puspa Pujia; Aulia Salsabila; Aulia Afiliyah Khasanah; Marsyah Fauziah; Yuspikarni Gulo (AKUNTANSI 45, 2025)
The advancement of digital technology has driven a significant transformation in how people conduct financial transactions. One of the most popular innovations is the use of e-wallets, which provide convenience and efficiency in transactions. This study aims to analyze the impact of e-wallet usage on financial management among employees of PT PNM, with consumer behavior serving as an intermediary variable. The research employs a quantitative method with regression analysis. The results show that e-wallet usage has a positive and significant impact on financial management. While e-wallets offer convenience in transactions, the study also found that usage without adequate financial awareness can lead to consumer behavior, which may disrupt personal financial stability. Therefore, financial literacy is crucial in the digital era to ensure that technologies like e-wallets are used wisely and effectively to support healthy personal financial management. The findings of this study provide valuable insights for companies and individuals to use digital technology more prudently, as well as highlight the importance of financial literacy education to raise financial awareness among society.